Institutional trust and economic policy : lessons from the history of the euro - Győrffy, Dóra (Central European University Press, 2013)
This book seeks to link theoretical debates on the relevance of trust in economic outcomes with arguments about the origins and lessons of the subprime crisis. By what mechanisms does trust influence economic outcomes? Under what conditions do these mechanisms prevail? How do debates about trust help our understanding of the subprime crisis in the European Union? By integrating insights from Post-Keynesian, Austrian and new institutional economics, the central proposition of the analysis is that the presence or absence of institutional trust creates virtuous and vicious cycles in law-abiding, which critically influence the possibility for economic agents to have realistic long-term plans.